Sepsis causes neutrophil infiltration in muscle leading to muscle atrophy and weakness in mice - Nakanishi, Nobuto; Ono, Yuko; Miyazaki, Yusuke; Moriyama, Naoki; Fujioka, Kazumichi; Yamashita, Kimihiro; Inoue, Shigeaki; Kotani, Joji (Frontiers in Immunology, 2022)
Background: Sepsis-induced muscle atrophy leads to prolonged physical dysfunction. Although the interaction of muscle atrophy and macrophage has been reported in sepsis, the role of neutrophils in muscle atrophy has not been thoroughly investigated. This study sought to investigate the long-term changes in muscle-localized neutrophils after sepsis induction and their possible role in sepsis. Methods: Sepsis was induced in seven-week-old male C57BL/6J mice 8-12 (cecal slurry [CS] model) via intraperitoneal injection of 1 mg/g cecal slurry. The percentage change in body weight and grip strength was evaluated. The tibialis anterior muscles were dissected for microscopic examination of the cross-sectional area of myofibers or Fluorescence-activated cell sorting (FACS) analysis of immune cells. These changes were evaluated in the following conditions: (1) Longitudinal change until day 61, (2) CS concentration-dependent change on day 14 at the low (0.3 mg/g), middle (1.0 mg/g), and high (2.0 mg/g) concentrations, and (3) CS mice on day 14 treated with an anti-Ly6G antibody that depletes neutrophils. Results: Body weight and grip strength were significantly lower in the CS model until day 61 (body weight: 123.1% ± 1.8% vs. 130.3% ± 2.5%, p = 0.04; grip strength: 104.5% ± 3.8% vs. 119.3% ± 5.3%, p = 0.04). Likewise, cross-sectional muscle area gradually decreased until day 61 from the CS induction (895.6 [606.0–1304.9] μm2 vs. 718.8 [536.2–937.0] μm2, p < 0.01). The number of muscle-localized neutrophils increased from 2.3 ± 0.6 cell/mg on day 0 to 22.2 ± 13.0 cell/mg on day 14, and decreased thereafter. In terms of CS concentration¬–dependent change, cross-sectional area was smaller (484.4 ± 221.2 vs. 825.8 ± 436.2 μm2 [p < 0.001]) and grip strength was lower (71.4% ± 12.8% vs. 116.3% ± 7.4%, p = 0.01) in the CS High group compared with the control, with increased neutrophils (p = 0.03). Ly6G-depleted mice demonstrated significant increase of muscle cross-sectional area and grip strength compared with control mice (p < 0.01). Conclusions: Sepsis causes infiltration of neutrophils in muscles, leading to muscle atrophy and weakness. These were reversed by neutrophil depletion. Neutrophils may play a critical role in sepsis-induced muscle atrophy and weakness.